Desalination and Sterilization of Sea Water Using Active Optimized Optical Heat Concentration System - Hifsa Shahid; Umar Rashid; Haris Anwaar; Muhammad Salim Butt; Fahim Gohar Awan; Farhan Ahmad Butt; Frederic Nzanywayingoma (IEEE Access, 2023)
Solar-powered desalination holds the potential to meet rising water needs. Most of the global desalination methods require a lot of electrical energy that mostly comes from non-renewable energy resources, including coal, natural gas, and oil. Carbon emissions from these sources cause breathing problems and ozone depletion. An empirical study is performed to evaluate the optically active desalination process. The suggested mechanism moves the light funnel axially regardless of incident light intensity to maintain the water reservoir temperature to a fixed level to perform desalination. To reduce tracking error, control systems with the triple-axis movement of Fresnel lenses are developed using an optimization algorithm employing the least-squares criterion. It also maintains the temperature of the water reservoir at 250°C by absorbing total incident irradiance through a copper slab by incorporating a customized nano honeycomb layer. A textured glass surface on top of the reservoir reduces solar reflections. The light rays are concentrated by top Fresnel lenses, while the bottom Fresnel lens produces a parallel beam of concentrated light that falls on a copper slab inside the reservoir, vaporizing the desalinated water to maintain a clean water supply. Total dissolved solids (TDS), the potential of hydrogen (pH), and microbial measurements are made before and after the desalination process. To increase the rate of desalination and decrease the boiling point of water, a low-pressure suction pump is used. This low-cost and environmentally friendly project produces pure drinking water and could be installed at any location.